ANALISIS PERAN KEAMANAN DATA DALAM MENINGKATKAN KEPUASAAN NASABAH PADA PENGGUNAAN MOBILE BANKING - Tursinah, Mar’atun; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This research analyzes the role of data security in increasing customer satisfaction when using mobile banking. With the rapid development of information technology, mobile banking has become customers' main choice in carrying out banking transactions. However, high data security risks can reduce the level of customer trust. Through survey methods and qualitative data analysis, this research identifies security factors that influence customer satisfaction, such as data encryption, two-factor authentication, and privacy protection. The results show that a good level of data security makes a significant contribution to customer satisfaction. Recommendations from this research include improving security systems by mobile banking service providers and educating customers about the importance of protecting personal data. Thus, data security not only protects customer information but also improves their experience and satisfaction in using digital banking services.